Power Generation Characteristics of Polymer Electrolyte Fuel Cells Using Carbon Nanowalls as Catalyst Support Material - Takayuki Ohta; Hiroaki Iwata; Mineo Hiramatsu; Hiroki Kondo; Masaru Hori (C, 2022)
We evaluated the power generation characteristics of a polymer electrolyte fuel cell (PEFC) composed of Pt-supported carbon nanowalls (CNWs) and a microporous layer (MPL) of carbon black on carbon paper (CP) as catalyst support materials. CNWs, standing vertically on highly crystallizing graphene sheets, were synthesized on an MPL/CP by plasma-enhanced chemical vapor deposition (PECVD) using inductively coupled plasma (ICP). Pt nanoparticles were supported on the CNW surface using the liquid-phase reduction method. The three types of voltage loss, namely those due to activated polarization, resistance polarization, and diffusion polarization, are discussed for the power generation characteristics of the PEFC using the Pt/CNWs/MPL/CP. The relationship between the height or gap area of the CNWs and the voltage loss of the PEFC is demonstrated, whereby the CNW height increased with the extension of growth time. The three-phase interface area increased with the increase in the CNW height, resulting in mitigation of the loss due to activated polarization. The gap area of the CNWs varied when changing the CH4/H2 gas ratio. The loss due to diffusion polarization was reduced by enlarging the gap area, due to the increased diffusion of fuel gas and discharge of water. The secondary growth of the CNWs caused the three-phase interface area to decrease as a result of platinum aggregation, impedance of the supply of ionomer dispersion solution to the bottom of the CNWs, and inhibition of fuel gas and water diffusion, which led to the loss of activated and diffuse polarizations. The voltage losses can be mitigated by increasing the height of CNWs while avoiding secondary growth.